Analysis of Community Income Inequality in Java Island - Ida Nuraini; Edwin Dermawan Sudarma (Trunojoyo University of Madura, 2025)
This study aims to find out the analysis of Income Inequality in the community in Java province in 2019-2023. The analysis unit covers six provinces using secondary data obtained from the Central Statistics Agency of Indonesia. The Dependent Variable in this study is the Gini Ratio and, the Independent Variables are Poverty, Labor Force Participation Rate and Unemployment. The analysis tool used is the Data Panel Regression with the Fixed Effect method. The results of the study show that 1) poverty has a positive and significant effect on income inequality, 2) the labor force participation rate has a positive and significant effect on income inequality and 3) unemployment has a negative and significant effect on income inequality (gini ratio). Therefore, provincial governments on the island of Java should expand access and improve skills that are in line with the needs of the labor market. Further research is expected to use a more comprehensive approach by adding more in-depth variables, in order to better understand the dynamics of income inequality.